Social networking sites usage trends among generation Y on mobile / Rosadilla Rosli - Rosli, Rosadilla (2015)
Social Networking sites (SNSs) is describe as any web site that enables users to form relationships to create public profiles and to communicate with other users of the same web site who access their profile within that web site (Vangie Beal, 2012). Recent years, social network sites have become popular particularly with young students (Mahe Bushra, 2010). Young students are called as Generation Y where those students who born between 1980 and 1995 and they are known as digital natives who have never known a world without computers (Ruth N. Bolton, 2013). Social network sites have become an integral part of Generation Y lives and help to build their connections with others (Alison M. Wolfe, 2000). Social media usage is particularly high among young adults and college students (Lenhart et al., 2010). Unfortunately, there are many web pages are deliberately spreading various slander and gossip and it may affect harmony and unification of our country. This spread negative propaganda may lead to chaos and anxiety community. All written material in SNSs able to trigger misunderstanding between peoples and caused negative behavior in this country easily. In the study, it was found out that generation Y uses social media as a media interaction, entertainment, and personal identity formation, sharing of information and media as well as online engagement. The results obtained show the factor that influence social media usage is personal factors (Ika Destiana, Ali Salman & Mohd Helmi, 2013). Prior research on the social media usage of Generation Y focuses primarily on the United States has discussed how Generation Y's use of social media influences individuals, firms and society. Ruth N Bolton has highlighted the dark side effect to the generation Y due to the individual factor.